2006
DOI: 10.1097/01.mco.0000214565.67439.83
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitors: what went wrong?

Abstract: These events provide a case study of a failure of the medical journal literature to guide drug usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…However, some recent studies have demonstrated that COX-2 specific inhibitors as well as conventional NSAIDs have potential side effects (Graham et al, 2002) and induce hypertension, a common management problem in cancer patients (Yancik et al, 1996). According to a recent report by James and Cleland (2006) selective COX-2 inhibitors can increase cardiovascular risks and thus are unsafe for clinical use. However, in our study, vitamin C showed a distinct effect on the suppression of COX-2 expression.…”
Section: Discussionmentioning
confidence: 98%
“…However, some recent studies have demonstrated that COX-2 specific inhibitors as well as conventional NSAIDs have potential side effects (Graham et al, 2002) and induce hypertension, a common management problem in cancer patients (Yancik et al, 1996). According to a recent report by James and Cleland (2006) selective COX-2 inhibitors can increase cardiovascular risks and thus are unsafe for clinical use. However, in our study, vitamin C showed a distinct effect on the suppression of COX-2 expression.…”
Section: Discussionmentioning
confidence: 98%
“…While the risk profile that lead to the withdrawal of rofecoxib might be indicative of aCOX-2 class effect [11,19,55], this may not have been the understanding of many prescribers (or consumers) for this group of community living older Australian women. This interpretation of COX-2 class risk has also varied across international studies of prescribing following the rofecoxib discrediting event, with some studies demonstrating a prescriber response to a class effect [2,23,26,28,30], and some not [22,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…They note that maternal ingestion of nimuselide, a coxib, may cause kidney failure in the unborn child. James and Cleland (2006) present other telling points against the use of coxibs. For example, the pharmaceutical company marketing rofecoxib denounced clinical trial evidence showing that the drug increases cardiovascular risk, and prescriptions of celecoxib have been common despite the lack of improved upper gastrointestinal safety.…”
Section: Nsaids and Antacidsmentioning
confidence: 95%